Peningkatan Keterampilan Membaca Pemahaman Dengan Menggunakan Metode Pembelajaran Think Pair Share (TPS) - Purwono Purwono; Ramdhan Witarsa; Molli Wahyuni (Departement of Mathematics Education, 2022)
This research concerned on students’ reading comprehension using Think Pair Share (TPS) method. The objective of research is to know the improvement of students’ reading comprehension in reading kids story material when Think Pair Share (TPS) Method is applied in fifth grade at SD Negeri 003 Siabu. This research is Classroom Action Research. It has been conducted on May 2021. It conducted in six meetings. The subject of the research is students of fifth grade at SD Negeri 003 Siabu included of 26 students. The result of this research showed that Think Pair Share method can improve students’ reading comprehension in reading kids story material it proved from the comparison of students score in every cycle. In pre-cycle, 5 students or 19,2% that achieve score higher than KKM 70. In cycle I, it improved to be 15 students or 57,7%. In cycle II, 24 students or 92,3% have score higher than KKM. In conclusion, the use of Think Pair Share method can improve students’ reading comprehension of fifth grade at SD Negeri 003 Siabu in academic year of 2021/2022.